JENIS-JENIS IKAN YANG DITANGKAP DI MUARA SUNGAI SALIDO KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - Saputra, Joko Hendriyanto (STKIP PGRI Sumbar, 2014)
Fish is aquatic organisms that are susceptible to environmental changes, human activities affect waterquality, physical, chemical, or biological, that affect the life and the spread of the fish. Salido estuarypollution caused by domestic wastes, residual use of fertilizers and pesticides, that can pollute estuarieswater. Overfishing also occurs in estuaries Salido, so that some species of fish that live in the estuarybecomes rare. The increasing human population growth in the area, the less land, so that a change in thefunction of mangroves as residential and garden, causing of mangrove vegetation decreases. This study aimsto determine the species of fish and physical-chemical parameters of water in estuaries Salido. The study wasconducted from August to September 2014 in an estuary Salido District of IV Jurai District of PesisirSelatan. The method used is descriptive survey with purposive sampling, where sampling is divided into 3stations by different estuarine conditions. Activities during the study done in two stages, the first stage offishing in estuaries Salido, the second phase of identifying fish in Ecology Laboratory Department ofBiology, Faculty of Mathematics and Natural Sciences Andalas University, Padang. Based on the results, 17species from 3 orders and 11 families with 429 individuals. The results of this study indicate that manyspecies of fish are found is Ambassis marcracanthus 25.87%, Liza subviridis 19.81%, Gerres filamentosus11.88%, Caranx tille 8.39%. Physico-chemical parameters of water has an important role to support theexistence of fish such as temperature, pH, salinity, water transparency and speed of water flow.